Instilling Anti-Corruption Values ​​for Students of MI Al-Ikhwan Pekanbaru - Datin Amanda Salsabila; Sapna Silvia Zazila Wati; Nabilla Tasya; Dean Anandra; Dinda Fitrina Aryati (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
The development of the increasingly modern era, brings positive and negative influences on the young generation of Indonesia. The thing that is the center of attention today, of course, leads to the negative impacts of the development of the era. The impacts that can be seen clearly in the field, such as free association of teenagers, drugs, and brawls between students. So, to minimize the greater impact, the most appropriate effort lies in education. The world of education is one of the strong foundations for filtering things that are outside the norms of life in Indonesian society. Because with education, students are taught about the values ​​that can and cannot be done in life. This activity aims to instill an anti-corruption nature so that a young generation is created who are aware of and understand the dangers of corruption, forms of corruption that can be carried out in elementary schools. The method used in this writing uses a literature study approach carried out by researchers to collect information relevant to the topic or problem that will or is being studied. The results of this article discuss the instillation of anti-corruption values ​​by implementing the values ​​of honesty, concern for others, responsibility, respect for others, discipline, simplicity, and fighting spirit or persistence in learning and understanding what sanctions are received by corruptors.